Usability Testing of an Online Self-management Program for Adolescents With Juvenile Idiopathic Arthritis - Stinson, Jennifer; McGrath, Patrick; Hodnett, Ellen; Feldman, Brian; Duffy, Ciaran; Huber, Adam; Tucker, Lori; Hetherington, Ross; Tse, Shirley; Spiegel, Lynn; Campillo, Sarah; Gill, Navreet; et al. (JMIR Publications, 2010)
BackgroundA new bilingual (English and French) Internet-based self-management program, Teens Taking Charge: Managing Arthritis Online, for adolescents with arthritis and their parents was developed following a needs assessment. ObjectivesThis study explored the usability (user performance and satisfaction) of the self-management program for youth with juvenile idiopathic arthritis (JIA) and their parents to refine the health portal prototype. MethodsA qualitative study design with semi-structured, audio taped interviews and observation by a trained observer was undertaken with two iterative cycles to determine the usability (ease of use, efficiency, errors, and user satisfaction) of the user interface and content areas of the intervention. A purposive sample of English-speaking (n = 11; mean age = 15.4, standard deviation [SD] 1.7) and French-speaking (n = 8; mean age = 16.0, SD 1.2) adolescents with JIA and one of their respective parents/caregivers were recruited from 2 Canadian tertiary care centers. Descriptive statistics and simple content analyses were used to organize data into categories that reflected the emerging usability themes. ResultsAll of the participants had access to a computer/Internet at home; however, adolescents were more comfortable using the computer/Internet than their parents. Adolescents and parents provided similar as well as differing suggestions on how the website user interface could be improved in terms of its usability (navigation; presentation and control usage errors; format and layout; as well as areas for further content development). There were no major differences in usability issues between English- and French-speaking participants. Minor changes to the website user interface were made and tested in a second cycle of participants. No further usability problems were identified in the second iterative cycle of testing. Teens and parents responded positively to the appearance and theme of the website (ie, promoting self-management) and felt that it was easy to navigate, use, and understand. Participants felt that the content was appropriate and geared to meet the unique needs of adolescents with JIA and their parents as well as English- and French-speaking families. Many participants responded that the interactive features (discussion board, stories of hope, and video clips of youth with JIA) made them feel supported and "not alone" in their illness. ConclusionsWe describe the usability testing of a self-management health portal designed for English- and French-speaking youth with arthritis and their parents, which uncovered several usability issues. Usability testing is a crucial step in the development of self-management health portals to ensure that the various end users (youth and parents) have the ability to access, understand, and use health-related information and services that are delivered via the Internet and that they are delivered in an efficient, effective, satisfying, and culturally competent manner.